Eğitim Yöneticilerinin Bireysel Girişkenlik ve Etkin İletişim Davranışlarının Öğretmenlerin Dağıtık Liderlik Algısına Etkisi / The Effect of Individual Assertiveness and Effective Communication Behaviors of Education Managers on Distributed Leadership Perception of Teachers - Bayraktar, Osman; Fidan, Yahya; Şencan, Hüner (Journal of History Culture and Art Research, 2018)
Abstract Distributed leadership is a management approach that found itself an application field especially in educational institutions. In the research, the effect of self-assertiveness and effective communication behaviors on the distributed leadership perception in an educational institution that is a lifelong learning center is expected to be specified and how this effect changes according to seniority and education factors is tried to be determined. In the study, an analysis is conducted based on the data collected from 302 people where 151 of them are education center managers and 151 are teachers. The Self-Assertiveness Scale developed by Frese et. Al. (1997) is used to measure the self-assertiveness, and for distributed leadership, the Distributed Leadership scale, which is used by Duif, Harrison, and Dartel (2013) in their researches, is used for the distributed leadership. In order to specify the relationships and/or effects between the variables, correlation, regression analysis, t-test, and ANOVA analysis methods are used. In the examination, it is found that the data that belongs to the composite variables that define the average points of all the three scales that is used in the statistical and graphical evaluations, has a normal distribution (p>0,05). The age average of the participants is 41 and the management duration average is 9 years for the participants where 50% of them are teachers and 50% of them are education managers. The age average of the teachers is 37 and the duration of being a teacher is 10 years. In the research, it is determined that there is no effect of self-assertiveness, effective communication and self-assertiveness/effective communication moderator variables on the distributed leadership perception. The main hypothesis of the research, which is that the moderator variable that consists of self-assertiveness, effective communication, and self-assertiveness/effective communication would have an effect on the distributed leadership perception, is not proved statistically. As the seniority level increases in the management group, the point of the distributed leadership decreases and on the other hand, in the teachers’ group, as the seniority increases the average of the distributed leadership perception point increases. The average of the distributed leadership perception points of the participants has a slight difference according to the education level. Öz Dağıtık liderlik, özellikle eğitim kurumlarında uygulama alanı bulmuş bir yönetim yaklaşımıdır. Araştırmada hayat boyu öğrenme merkezi niteliği olan bir eğitim kurunda bireysel girişkenlik ve etkin iletişim davranışlarının hissedilen dağıtık liderlik algısı üzerindeki etkisi belirlenmek istenmiş; kıdem ve eğitim faktörlerine göre bu etkinin ne şekilde değişeceği saptanmaya çalışılmıştır. Çalışmada 151’i eğitim merkezi yöneticisi, 151’i öğretmen olmak üzere 302 kişiden toplanan veriler üzerinden analiz yapılmıştır. Bireysel girişkenliği ölçmek için Frese vd. (1997) tarafından geliştirilen Bireysel Girişkenlik Ölçeği, etkin iletişim için Takahashi, Tanaka ve Miyaoka (2006 tarafından geliştirilen İletişim Becerileri Ölçeği, dağıtık liderlik için Duif, Harrison ve Dartel’in (2013) araştırmalarında kullandıkları Dağıtık Liderlik Ölçeğinden yararlanılmıştır. Değişkenler arasındaki ilişkileri ve/veya etkiselliği belirlemek için korelasyon, regresyon analizi, t-testi ve ANOVA analiz yöntemlerinden yararlanılmıştır. Yapılan incelemede istatistiksel ve grafiksel değerlendirmelerde kullanılan her üç ölçeğin de ortalama puanlarını tanımlayan kompozit değişkenlere ait verilerin normal dağılım özelliği gösterdiği bulunmuştur (p > 0,05). Verilere göre katılımcıların (% 50’si öğretmen, %50’si eğitim merkezi yöneticisi grubunda yer alan katılımcıların yaş ortalaması 41, yöneticilik süresi ortalamaları 9’dur. Öğretmen grubunda yer alan katılımcıların yaş ortalaması 37, öğretmenlik süresi ortalaması 10 yıldır Araştırmada, bireysel girişkenlik, etkin iletişim ve bireysel girişkenlik-etkin iletişim modaratör bağımsız değişkenlerinin, hissedilen dağıtık liderlik algısı üzerinde etkisi olmadığı saptanmıştır. Araştırmanın temel hipotezi olan, bireysel girişkenlik, etkin iletişim ve bireysel girişkenlik-etkin iletişim etkileşiminden oluşan moderatör değişkeninin, hissedilen Dağıtık Liderlik algısını etkileyeceği savı istatiksel olarak kanıtlanamamıştır. Yönetici grubunda kıdem düzeyi arttıkça dağıtık liderlik puan algısı ortalaması düşmekte, öğretmenler grubunda ise kıdem arttıkça dağıtık liderlik puan algısı ortalaması da yükselmektedir. Katılımcıların dağıtık liderlik puan algısı ortalamaları eğitim düzeyine göre küçük farklılıklar göstermektedir.